A APRENDIZAGEM SIGNIFICATIVA DE AUSUBEL E A RELAÇÃO COM MATERIAIS ALTERNATIVOS NA DISCIPLINA DE GEOMETRIA MOLECULAR (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
This work is based on the construction of pedagogical models for the teaching of Chemistry from alternative materials. The content of Chemistry that will be addressed will be molecular geometry, which involves the arrangement of atoms and their connections in three-dimensional space forming geometric figures and angles specific to each link. It was chosen based on classroom observations of the difficulty felt by students in achieving visualize the molecules and their connections in the space. The molecular models are made from alternative material that facilitates the acquisition and with affordable price compared to the models commercialized in the market, besides enabling the student to construct its own knowledge through the real representation of the molecules presented during class.
Keywords: Teaching; Chemistry; Molecular Geometry; Alternative Materials